Software Composition 10th International Conference, SC 2011, Zurich, Switzerland, June 30 - July 1, 2011. Proceedings - Apel, Sven; Jackson, Ethan (Springer eBooks., 2011)
The book constitutes the refereed proceedings of the 10th International Conference on Software Composition, SC 2011, held in Zurich, Switzerland, in June/July 2011, co-located with TOOLS 2011 Federated Conferences.The 10 revised full papers and 2 short papers were carefully reviewed and selected from 32 initial submissions for inclusion in the book. The papers reflect all current research in software composition and are organized in topical sections on composition and interfaces, aspects and features, and applications.